Cold modalities with different thermodynamic properties have similar effects on muscular performance and activation - Vieira, A.; Oliveira, A. B.; Costa, J. R.; Herrera, E.; Salvini, T. F. (International Journal of Sports Medicine, 2013)
Although tissue cooling is widely used in the treatment of musculoskeletal injuries there is still controversy about its effects on muscular performance. The combination of cooling and exercise justifies the study of this topic. The aim was to compare the effects of ice pack and cold-water immersion on the muscular performance parameters of plantar flexors and muscular activation of the triceps surae. 41 healthy men (mean age: 22.1 years, SD: 2.9) were randomly assigned to cooling with either ice pack (n=20) or cold-water immersion (n=21). Independent variables were cold modality (ice pack or cold-water immersion) and pre- and post-cooling measurement time. Dependent variables were muscular performance (measured during isometric and concentric contractions of plantar flexors) and electromyography parameters of the triceps surae (median frequency and root mean square amplitude). Dependent-samples t-tests were used to compare pre- and post-cooling data and independent-samples t-tests were used to compare the difference (pre- and post-cooling) between groups. Ice pack increased isometric peak torque (mean: 9.00 Nm, P=0.01) and both cold modalities reduced muscular activation in triceps surae (P<0.0001); Cold-water immersion and ice pack reduced peak torque and total work during dynamic isokinetic contraction at both velocities (mean: -11,00 Nm, P<0.05) and affected muscular activation in different ways. In conclusion, ice pack increases isometric torque, while both ice pack and cold-water immersion decrease concentric muscular performance. These results indicate that these cooling methods should be chosen with caution, considering the type of task required during training or rehabilitation. New studies investigating other muscle groups and joints are necessary.